FETAL DISCORDANCY IN MONOCHORIONIC TWINS - L. G. Sichinava; O. B. Panina; K. G. Gamsakhurdiya (Акушерство, гинекология и репродукция)
Objective: to investigate the predictive value of fetal weight discordance as a risk factor associated with adverse perinatal outcomes. Materials and Methods: 55 patients with monochorionic diamniotic twin pregnancies with fetal weight discordancy were analyzed. All patients underwent ultrasound examination in the 1st trimester of pregnancy (11-14 weeks) to confirm the chorionicity. Estimated fetal weight discordance was calculated as (larger estimated fetal weight - smaller estimated fetal weight) / larger estimated fetal weight. All monochorionic patients were divided into the groups according to the differences in birthweight in twins (≤10%, >10 ≤15%, >15 ≤20%, ≤20 ≤25%, >25%). Adverse perinatal outcomes included: preterm delivery rate (≤34 weeks), fetal distress, low Apgar score, perinatal death, pathological neurosonographic findings. Results: severe birthweight discordance (>20%) in our study was associated with the highest risk of prematurity (76.2%), IUGR (47.6%), fetal distress and low Apgar score (75.0%), pathological neurosonographic findings (46.3%). These adverse perinatal outcomes were more pronounced in the group of monochorionic patients with birthweight discordance greater than 25%. Fetal weight discordance (>20%) is associated with the high risk of adverse perinatal outcomes and twin pregnancies with this complication require careful antenatal monitoring and timing of delivery.